GENETIC STUDIES FOR SOME YIELD-RELATED TRAITS IN OKRA (ABELMOSCHUS ESCULENTUS L.) - KHAN, F; KAYNAT, A; SAEED, A; JAVAID, T; IQBAL, RA; LATIF, A; NAWAZ, MS; LATIF, A; SIDDIQUI, GM; HASSAN, A; JAVED, HM (Biological and Clinical Sciences Research Journal, 2024)
Okra is a traditional vegetable famous for its nutritional value. It is a perfect villager’s vegetable due to its robust nature, dietary fiber, and seed protein balance of both tryptophan and lysine. The research was carried out in the research area of the Department of Plant Breeding and Genetics, University of Agriculture Faisalabad. Cross combinations among 3 lines (Patel, Selection Super Green, and 19234) and 3 testers (IQRA-III, Perbhani Karanti, and Sabz Pari) were developed by using line × tester design. Crossed seeds along with parents were grown in the field under Randomized Complete Block Design (RCBD) with three replications. Data for various morphological traits was collected and analyzed statistically through analysis of variance and used to assess GCA, SCA, and gene action. Genotype 19234 exhibited maximum significant GCA (-11.4) for plant height in the negative direction and genotype Selection super Green proved a good general combiner for fruit weight, fruit diameter, and first flowering node, exhibiting values of 3.21, 1.191, and -0.89. IQRA-III (3.00), Patel (2.00), and Perbhani Karanti (1.11) exhibited significant GCA for number of fruits per plant. Line 19234 observed a good general combiner for crude fat (0.28), ash (5.43), and protein (0.39). Cross combination Patel × Perbhani exhibited the highest SCA for the number of fruits (7.78) followed by Selection Super Green × Sabz Pari (4.78) hence can be exploited for heterosis breeding. Cross combination Selection Super Green × Perbhani Karanti exhibited the highest significant SCA for plant height (-7.60) and Selection Super Green × IQRA-III displayed the maximum significant SCA value (2.26) for crude fat. Line Patel proved a good general combiner for most of the yield-related traits. Based on GCA and SCA, line 19234 can be used to enhance quality traits and cross combination Patel × Perbhani Karanti can be used to increase the number of fruits per plant.